Assessment of bio-inoculants-mediated nutrient management in terms of productivity, profitability and nutrient harvest index of pigeon pea–wheat cropping system in India. (20th August 2020) - Gupta, Gaurendra; Dhar, Shiva; Dass, Anchal; Sharma, Vinod Kumar; Shukla, Livleen; Singh, Renu; Kumar, Adarsh; Kumar, Amit; Jinger, Dinesh; Kumar, Dinesh; S. Sannagoudar, Manjanagouda; Kumar Kamboj, Navish; et al.
Abstract: Imbalanced and indiscriminate use of chemical fertilizers has been adversely influencing the quality of soil, environment, biodiversity and nutrient status in soil. Conjoint application of bio-inoculants (BI) with organic or inorganic sources of nutrients tweaks nutrient synchrony in soil and improves plant nutrition. With this backdrop an experiment was conducted at Indian Agricultural Research Institute, New Delhi during 2016–2018. The objectives were to identify the suitable combinations of BI-mediated nutrient sources for higher productivity and profitability in pigeon pea–wheat cropping system (PWCS). The nine pigeon pea treatments; four sole applications viz ., recommended dose of fertilizers (RDF), vermicompost (VC), farm yard manure (FYM), leaf compost (LC) and four conjoint applications viz., RDF + BI, VC + BI, FYM + BI and LC + BI and one control were replicated thrice under randomized block design (RBD). However, in succeeding wheat, each of the treatments applied to pigeon pea was further allocated to two levels (50% and 100%) in factorial RBD. Findings exhibit that FYM + BI could result into higher equivalent-system grain productivity (10.4 and 10.8 t ha −1 during 1st and 2nd year, respectively) of PWCS. However, profitability parameters of PWCS were higher with the RDF + BI. Uptake of nutrients (NPK) was significantly higher with FYM + BI in pigeon pea and RDF + BI in wheat. Nutrient harvest index (NHI) did not vary significantly in both the crops. Conclusively, bio-inoculation is more productive and beneficial in general, while, over the various combinations, recommendation of FYM + BI combination could be more productive and sustainable.